Weight method for determination of soluble β-glucans in barley grain - V. S. Popov; A. V. Konarev; O. N. Kovaleva; N. G. Konkova; V. I. Khoreva (Труды по прикладной ботанике, генетике и селекции)
Background. Barley (Hordeum vulgare L.) is an important source of nutrients, such as starch, protein, and various dietary fibers. β-Glucans are soluble fibers found in high amounts in oat and barley grain, so they are becoming increasingly interesting due to their numerous functional and bioactive properties. The increased interest in β-glucans as a dietary supplement and a functional component of food calls for a convenient, inexpensive and affordable method for quantitative determination of these compounds.Materials and methods. An overview is given on the existing techniques for determining and isolating β-glucans in cereals: IR spectroscopy, enzymatic, colorimetric, and alkaline-enzymatic methods. Their advantages and disadvantages are shown. The disadvantages of the methods considered include high costs of reagents and equipment, duration of performance, and labor intensity.Results. This study promotes the weight method for isolation and quantitative determination of β-glucans in the grain of covered and naked barley. It is based on the modified alkaline method adapted to barley; we developed it earlier for oat grain. The amount of β-glucans in the grain of the studied barley accessions ranged from 4.12±0.23% to 5.34 ± 0.31% for naked cultivars, and from 3.57 ± 0.18% to 4.29 ± 0.32% for covered ones.Conclusion. Based on the conducted research, optimal conditions for the isolation and quantitative determination of β-glucans from barley grain were selected: centrifugation modes, temperature and extraction ratio, concentration of compounds, precipitation and drying procedures. The main advantage of the described method is its accessibility and practical applicability when conducting mass analysis, including studying a collection of cereal crops.